1998
DOI: 10.1038/sj.leu.2400925
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia cells with low P-glycoprotein expression and high Rhodamine 123 efflux capacity display high clonogenicity

Abstract: This study was designed to correlate the clonogenic capacity of acute myeloid leukemia (AML) cells with P-glycoprotein (Pgp) expression level and P-gp-mediated efflux capacity. Fifty AML cell samples were tested for P-gp expression using MRK16 monoclonal antibody and flow cytometry. Among them, 12 samples were selected for sorting experiments according to the following two criteria: their clonogenic capacity in methylcellulose in the presence of 5637 conditioned medium, and the heterogeneity of P-gp distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…5 Here we hypothesized that the 3435C.T SNP in the ABCB1 gene can modulate the immunosuppressive activity of tacrolimus by altering the activity of the pump. [18][19][20] The T cells with the highest ABCB1 efflux activity are memory CD4 + and CD8 + T cells, 9,21 a population with low susceptibility to tacrolimus 22 and important in the transplantation setting because they are pivotal for alloreactivity. 2).…”
Section: Discussionmentioning
confidence: 99%
“…5 Here we hypothesized that the 3435C.T SNP in the ABCB1 gene can modulate the immunosuppressive activity of tacrolimus by altering the activity of the pump. [18][19][20] The T cells with the highest ABCB1 efflux activity are memory CD4 + and CD8 + T cells, 9,21 a population with low susceptibility to tacrolimus 22 and important in the transplantation setting because they are pivotal for alloreactivity. 2).…”
Section: Discussionmentioning
confidence: 99%
“…The specific role of Pgp modulators and their kinetic profile is thus essential to fully characterize and approach the broad properties of immunosuppressive drugs (31), Laurent G et al (32) and Gupta et al (33) clearly showed that the expression of Pgp was higher in CD4 + than in CD8 + T cells. Functionally, Pgp was more efficient in the CD8 + subpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23] Briefly, 3 Â 10 5 cells were resuspended in methyl-cellulose semi-solid medium with (PE1 þ , Plating Efficiency at 1 week) or without (PE1-) 10% human bladder carcinoma cell line 5637 conditioned medium (5637 CM). A total of 1 Â 10 5 cells was then plated in 35 mm Petri dishes in triplicate (1 ml mixture/dish), and incubated at 371C and 5% CO 2 humidified atmosphere.…”
Section: Clonogenic Assaysmentioning
confidence: 99%